About how to capture and exploit the CO2 surplus that nature, per se, is not capable of fixing. Issue 5 (14th August 2017) - Godoy, Manuel S.; Mongili, Beatrice; Fino, Debora; Prieto, M. Auxiliadora
Summary: Human activity has been altering many ecological cycles for decades, disturbing the natural mechanisms which are responsible for re‐establishing the normal environmental balances. Probably, the most disrupted of these cycles is the cycle of carbon. In this context, many technologies have been developed for an efficient CO2 removal from the atmosphere. Once captured, it could be stored in large geological formations and other reservoirs like oceans. This strategy could present some environmental and economic problems. Alternately, CO2 can be transformed into carbonates or different added‐value products, such as biofuels and bioplastics, recycling CO2 from fossil fuel. Currently different methods are being studied in this field. We classified them into biological, inorganic and hybrid systems for CO2 transformation. To be environmentally compatible, they should be powered by renewable energy sources. Although hybrid systems are still incipient technologies, they have made great advances in the recent years. In this scenario, biotechnology is the spearhead of ambitious strategies to capture CO2 and reduce global warming. Abstract : The tremendous impacts of global warming are being felt all over the world due to humans unsustainable way of life. We have released to the atmosphere more CO2 than what Nature has been capable of fixing. Different approaches are being implemented to diminish this environmental problem. In this study we aim to update the most promising biotechnological approaches to capture and exploit excess of CO2 to accomplish human beings quality of life integrated to the sustainability of our planet.